Extrahierung von Anforderungen aus natürlich-sprachlichen Lastenheften: Was erschwert eine KI-basierte Extrahierung? - Gräßler, Iris; Preuß, Daniel; Pottebaum, Jens (Softwaretechnik-Trends)

Energy saving potentials of an efficient recycling process of different aluminum rejects - Borgert, Thomas; Homberg, Werner (Energy Reports)
Keywords: General Energy

Review on mechanical joining by plastic deformation - Meschut, G.; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, W.; Martins, P.A.F.; Bobbert, M.; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Hot Spinning of Cutting Blades for Food Industry - Engemann, David; Homberg, Werner
The spinning process is a flexible incremental forming process for the manufacturing of axially-symmetric sheet metal or tubular components with functionally graded properties. It is characterized by the utilization of universal tooling geometries and quite low forming forces. The process has a high potential to reduce material waste, to extend the forming limits and to achieve more complex geometries as well as favorable part properties [1]. Current research work at the Chair of Forming Technology (LUF) is focused on innovative flow-turning processes that have a high potential for producing flat components with excellent geometrical and mechanical properties while keeping process times short [2]. In combination with process-integrated local heat treatment, the new spinning process is predestined for the efficient forming of ultra-high-strength steel or tailored materials. Due to the desired field of food industry only food-safe materials such as special stainless steels are being investigated. This paper presents an innovative machine layout as well as an adequate process design for the production of high-performance circular knives with optimized mechanical hardness. In this context, particular attention is paid to various areas of temperature control as well as process-related challenges during the process.
Keywords: Cutting blades; Flow-forming; Incremental forming; Hot Forming; High strength steels

Identification of Requirements for FE Modeling of an Adaptive Joining Technology Employing Friction-Spun Joint Connectors (FSJC) - Oesterwinter, Annika; Wischer, Christian; Homberg, Werner (Metals)
The adaptive joining process employing friction-spun joint connectors (FSJC) is a promising method for the realization of adaptable joints and thus for lightweight construction. In addition to experimental investigations, numerical studies are indispensable tools for its development. Therefore, this paper includes an analysis of boundary conditions for the spatial discretization and mesh modeling techniques, the material modeling, the contact and friction modeling, and the thermal boundary conditions for the finite element (FE) modeling of this joining process. For these investigations, two FE models corresponding to the two process steps were set up and compared with the two related processes of friction stir welding and friction drilling. Regarding the spatial discretization, the Lagrangian approach is not sufficient to represent the deformation that occurs. The Johnson-Cook model is well suited as a material model. The modeling of the contact detection and friction are important research subjects. Coulomb’s law of friction is not adequate to account for the complex friction phenomena of the adaptive joining process. The thermal boundary conditions play a decisive role in heat generation and thus in the material flow of the process. It is advisable to use temperature-dependent parameters and to investigate in detail the influence of radiation in the entire process.
Keywords: General Materials Science; Metals and Alloys

Further Development of an Adaptive Joining Technique Based on Friction Spinning to Produce Pre-Hole-Free Joints - Wischer, Christian; Homberg, Werner (Key Engineering Materials)
Mechanical joining processes are an essential part of modern lightweight construction. They permit materials of different types to be joined in a way that is suitable for the loads involved. These processes reach their limits, however, as soon as the boundary conditions change. In most cases, these elements are specially adapted to the joining point and cannot be used universally. Changes require cost-intensive adaptation of both the element and the process control, thus making production more complex. This results in high costs due to the increased number of auxiliary joining element variants required and reduces the economic efficiency of mechanical joining. One approach to overcoming this issue is the use of adaptive auxiliary joining elements formed by friction spinning. This article presents the current state of research on pre-hole-free joining with adaptive joining elements. The overall process chain is illustrated, explained and analyzed. Special attention is paid to demonstrating the feasibility of pre-hole-free joining with adaptive joining elements. The chosen mechanical parameters are subsequently listed. Finally, a comprehensive outlook of the future development potential is derived.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Comparative Analysis of Electrohydraulic and Electromagnetic Sheet Metal Forming against the Background of the Application as an Incremental Processing Technology - Heggemann, Thomas; Psyk, Verena; Oesterwinter, Annika; Linnemann, Maik; Kräusel, Verena; Homberg, Werner (Metals)
High-speed forming processes such as electromagnetic forming (EMF) and electrohydraulic forming (EHF) have a high potential for producing lightweight components with complex geometries, but the forming zone is usually limited to a small size for equipment-related reasons. Incremental strategies overcome this limit by using a sequence of local deformations to form larger component areas gradually. Hence, the technological potential of high-speed forming can be exploited for large-area components too. The target-oriented process design of such incremental forming operations requires a deep understanding of the underlying electromagnetic and electrohydraulic forming processes. This article therefore analyzes and compares the influence of fundamental process parameters on the acting loads, the resulting course of deformation, and the forming result for both technologies via experimental and numerical investigations. Specifically, it is shown that for the EHF process considered, the electrode distance and the discharge energy have a significant influence on the resulting forming depth. In the EHF process, the largest forming depth is achieved directly below the electrodes, while the pressure distribution in the EMF depends on the fieldshaper used. The energy requirement for the EHF process is comparatively low, while significantly higher forming speeds are achieved with the EMF process.

Automated Requirement Dependency Analysis for Complex Technical Systems - Gräßler, Iris; Oleff, Christian; Hieb, Michael; Preuß, Daniel (Proceedings of the Design Society)
Abstract Requirements changes are a leading cause for project failures. Due to propagation effects, change management requires dependency analysis. Existing approaches have shortcomings regarding ability to process large requirement sets, availability of required data, differentiation of propagation behavior and consideration of higher order dependencies. This paper introduces a new method for advanced requirement dependency analysis based on machine learning. Evaluation proves applicability and high performance by means of a case example, 4 development projects and 3 workshops with industry experts.

Mensch-Tracking zur Identifizierung des Voranschreitens von Roboterunterstützten Rettungseinsätzen der Feuerwehr - Gräßler, I.; Roesmann, Daniel; Pottebaum, Jens; Corves, Burkhard; Mandischer, Nils; Gürtler, Marius (Tagungsband der VDI Mechatronik 2022)

Extended RFLP for complex technical systems - Gräßler, Iris; Wiechel, Dominik; Oleff, Christian

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Influence of plane mixed-mode loading on the kinking angle of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

A statistically based strain energy function for polymer chains in rubber elasticity - Mahnken, Rolf; Mirzapour, Jamil (Archive of Applied Mechanics)
Keywords: Mechanical Engineering

Effects on Process Forces of Individual Milling Tool Edges Depending on the Cutting Angle and Cutting Speed When Milling Cfrp - Clemens, Robin; Barth, Enrico; Uhlmann, Eckart; Zhan, Yingjie; Caylak, Ismail; Mahnken, Rolf (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Innendrückwalzen – Ein innovatives Umformverfahren zur inkrementellen Formgebung von wanddickenkonturierten Rohren mit lokal einstellbaren mechanischen Eigenschaften - Wiens, Eugen

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)